Indicators accounting for the variability, in humid basis, among Pennisetum purpureum clones - Herrera, Rafael Segundo; Garc?a, Manuel; Fortes, Daileny; Cruz, Ana M.; Romero, Aida (Cuban Journal of Agricultural Science, 2013)
An experiment was carried out to determine the agronomical indicators, expressed in humid basis, most contributing to account for the variability in 49 clones of Pennisetum purpureum, obtained by in vitro tissue culture from the apical tissue of P. purpureum cv. Cuba CT-115. A completely random design with five replications was applied. The experiment lasted one year. The analysis of the main components indicated that in the rainy period two components accounted for 81.65% of the variability among clones integrated by height, leaf and stem contents and length of the fourth leaf completely opened, internode length and fresh matter yield. In the dry period two main components accounted for 84.68% of the variability between clones integrated by the same indicators than in the rainy period. It is concluded that the above mentioned indicators, expressed in humid basis, can be used for establishing the variability among Pennisetum clones. This determines savings in time and resources, without losing the quality and scientific rigor in the research. Similar studies are recommended under different environmental conditions and with other pasture varieties including other indicators. Key words: multivariate analysis, agronomical indicators, Pennisetum